Tinjauan Al-Quran dan Hadist Tentang Manajemen Layanan dan Prinsipnya: Studi Literatur - Liza, Nova; Gumsi, Putri Eka; Satriadi, Inong (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article presents an analysis of the relationship between service management in the context of Islamic education with principles taken from verses of the Qur'an and hadith of the Prophet Muhammad (PBUH). Service management is seen as a key element in the management of Islamic educational institutions to provide the best experience to learners, educators, and other related parties. The type of research used is a literature study. The source of research data comes from various relevant literature including the Quran and hadith, books, and scientific articles. Data analysis techniques are carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of data analysis show that service management in the context of Islamic education management is an approach used to manage services or facilities related to the implementation of Islamic education. Key principles such as honesty, fairness, responsibility, and empathy, found in Islamic sources, are analyzed in the context of their application in educational management. In addition, the importance of communication skills, leadership, as well as planning, implementing, and evaluating educational programs that are in line with Islamic teachings are also clarified. Taking these principles into account, managers of educational institutions can ensure the overall and sustainable achievement of Islamic educational goals, as well as make a meaningful contribution in the formation of character and morality of learners in accordance with Islamic values